EKSISTENSI AGUNAN DALAM PEMBIAYAAN BANK UMUM SYARIAH DI DENPASAR - Setyawan Nugroho, Ade; Puspawati, I Gusti Ayu; Putra Atmadja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
This scientific study entitled Collateral In Islamic Banks Financing,motivated by a fact that many financing activities that do not run smoothlybecause the customer is unable to meet its obligations to the bank. To prevent this,Islamic banks are required to apply the precautionary principle, one of whichincludes collateral for customers who submit funding recipients. The purpose ofthis study was to find out the existence of collateral in the Islamic banks financingand to find out actions of Islamic banks in terms of customer facilities recipientwhich does not meet its obligations to the bank. This research was a legalresearch which used empirical legal research methods by conducting researchdirectly in Denpasar. As a conclusion, it was found that the collateral in financingof Islamic banks was essential thing that must exist, it became a virtue that bankshave certainty and guarantee the repayment obligations of the receiving facilitycustomers. In case of the customer could not meet its obligations to the bank,then the action taken Islamic banks were taking action in the form of rescuing thefinancial by rescheduling, reconditioning, and restructuring, and if such effortsstill can not resolve the problem then the next action bank will pursue financialtroubles by executing collateral.
Keywords: Collateral, Financial, Islamic Banks